Enhancing the Shelf Life of Sous-Vide Red Deer Meat with Piper nigrum Essential Oil: A Study on Antimicrobial Efficacy against Listeria monocytogenes - Kačániová, Miroslava; Čmiková, Natália; Ban, Zhaojun; Garzoli, Stefania; Elizondo-Luevano, Joel Horacio; Ben Hsouna, Anis; Ben Saad, Rania; Bianchi, Alessandro; Venturi, Francesca; Kluz, Maciej Ireneusz; Haščík, Peter (Molecules (Basel, Switzerland), 2024)
Using sous-vide technology in combination with essential oils offers the potential to extend the preservation of food items while preserving their original quality. This method aligns with the growing consumer demand for safer and healthier food production practices. This study aimed to assess the suitability of minimal processing of game meat and the effectiveness of vacuum packaging in combination with Piper nigrum essential oil (PNEO) treatment to preserve red deer meat samples inoculated with Listeria monocytogenes. Microbial analyses, including total viable count (TVC) for 48 h at 30 °C, coliform bacteria (CB) for 24 h at 37 °C, and L. monocytogenes count for 24 h at 37 °C, were conducted. The cooking temperature of the sous-vide was from 50 to 65 °C and the cooking time from 5 to 20 min. Additionally, the study monitored the representation of microorganism species identified through mass spectrometry. The microbiological quality of red deer meat processed using the sous-vide method was monitored over 14 days of storage at 4 °C. The results indicated that the TVC, CB, and L. monocytogenes counts decreased with the temperature and processing time of the sous-vide method. The lowest counts of individual microorganism groups were observed in samples treated with 1% PNEO. The analysis revealed that PNEO, in combination with the sous-vide method, effectively reduced L. monocytogenes counts and extended the shelf life of red deer meat. Kocuria salsicia, Pseudomonas taetrolens, and Pseudomonas fragi were the most frequently isolated microorganism species during the 14-day period of red deer meat storage prepared using the sous-vide method.